Industrial Relations Bill cartoon, 1971 (1971)
1971 1960-2000 "Industrial Relations Bill cartoon, 1971" [T0432.jpg], 1971, Trades Union Congress, Heath Cartoon from a TUC pamphlet opposing the 1971 Industrial Relations Bill.